AP physics 2 premium prep (Penguin Random House, 2024)
"Ace the newly-updated AP Physics 2 Exam with this comprehensive study guide--including 3 full-length practice tests (2 in the book, 1 online) with complete explanations, content reviews, exam strategies, and access to online extras"--